2011
DOI: 10.2337/db11-0255
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial NO/cGMP/VASP Signaling Attenuates Kupffer Cell Activation and Hepatic Insulin Resistance Induced by High-Fat Feeding

Abstract: OBJECTIVEProinflammatory activation of Kupffer cells is implicated in the effect of high-fat feeding to cause liver insulin resistance. We sought to determine whether reduced endothelial nitric oxide (NO) signaling contributes to the effect of high-fat feeding to increase hepatic inflammatory signaling and if so, whether this effect 1) involves activation of Kupffer cells and 2) is ameliorated by increased NO signaling.RESEARCH DESIGN AND METHODSEffect of NO/cGMP signaling on hepatic inflammation and on isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
158
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(166 citation statements)
references
References 33 publications
8
158
0
Order By: Relevance
“…The character of the accumulated macrophages in LT Ϫ/Ϫ mice was likely to be weighted toward an M2 transcript profile due to elevated levels of markers MGL1 and Arg1 for chow-fed mice and decreased levels of TNF for both diets in LT Ϫ/Ϫ as opposed to WT adipose tissue (34). The M2 phenotype is thought to be anti-inflammatory in nature (69) and not associated with insulin resistance, although we did see a preponderance of Arg1 mRNA for WT HFHS diet-fed mice in our study. This may be due to experimental design since macrophage phenotype marker expression is dynamic and influenced by diet duration (62).…”
Section: Most Importantly Hfhs Diet Feeding Of Ltmentioning
confidence: 99%
“…The character of the accumulated macrophages in LT Ϫ/Ϫ mice was likely to be weighted toward an M2 transcript profile due to elevated levels of markers MGL1 and Arg1 for chow-fed mice and decreased levels of TNF for both diets in LT Ϫ/Ϫ as opposed to WT adipose tissue (34). The M2 phenotype is thought to be anti-inflammatory in nature (69) and not associated with insulin resistance, although we did see a preponderance of Arg1 mRNA for WT HFHS diet-fed mice in our study. This may be due to experimental design since macrophage phenotype marker expression is dynamic and influenced by diet duration (62).…”
Section: Most Importantly Hfhs Diet Feeding Of Ltmentioning
confidence: 99%
“…In addition, the hepatic triacylglycerol content of VASP knockout mice was higher than that of WT mice [14]. Furthermore, an in vitro study showed that lipopolysaccharide-induced expression of TNFα or iNOS in macrophages is attenuated in the presence of agents that increase VASP signaling, such as diazen-1-IM1, 2-diolate, and 8-bromoguanosine-3′,5′-cGMP [14]. Similarly increases in TNFα or iNOS expression induced by combined treatment with lipopolysaccharide and interferon γ were attenuated in macrophages that overexpressed VASP [14].…”
Section: Immunohistochemistrymentioning
confidence: 87%
“…Recently, it was reported that the expression of proinflammatory markers in the Kupffer cells of VASP knockout mice was significantly higher than that of WT mice. In addition, the hepatic triacylglycerol content of VASP knockout mice was higher than that of WT mice [14]. Furthermore, an in vitro study showed that lipopolysaccharide-induced expression of TNFα or iNOS in macrophages is attenuated in the presence of agents that increase VASP signaling, such as diazen-1-IM1, 2-diolate, and 8-bromoguanosine-3′,5′-cGMP [14].…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations